Methylglyoxal induces oxidative stress and ferroptosis of renal tubular epithelial cells in acute and chronic kidney injury mice - Zhang, Yongzheng; Zhang, Xuwu; Ren, Jiayu; Sun, Hao; Yang, Zhe; Wang, Jianning (Frontiers in Cell and Developmental Biology, 2025)
Methylglyoxal (MG), which is a highly reactive dicarbonyl compound, has been increasingly recognized due to its role in the pathogenesis of kidney injury, particularly in diseases such as diabetic nephropathy and hypertensive nephropathy. MG promotes advanced glycation end product (AGE) formation and directly impairs cell function. MG levels are significantly increased in various renal diseases. This study aimed to investigate the relationship between MG and ferroptosis, which is a form of cell death involving iron-dependent lipid peroxidation (LPO), during kidney injury. Animal and cellular experiments were conducted to verify that ferroptosis occurred after MG treatment, and RNA sequencing (RNA-Seq) was performed to analyse changes in gene expression profiles after MG exposure. A mouse model that mimicked human kidney injury was established by administering folic acid, and the MG and D-lactate levels in serum and tissues were measured. In vitro experiments involved treating human HK-2 renal tubular epithelial cells (TECs) with MG and assessing markers of cytotoxicity, oxidative stress, and ferroptosis. MG levels were significantly increased in serum and renal tissues from patients with renal injury and from model mice. In HK-2 cells, MG treatment induced cytotoxicity, increased intracellular reactive oxygen species (ROS) levels, triggered ferroptosis by increasing LPO, and decreased glutathione (GSH) levels. These findings suggest a potential association between MG accumulation and kidney injury and indicate that MG promotes ferroptosis specifically in renal TECs. This study provides new insights into the molecular mechanisms underlying MG-induced kidney injury and potential directions for developing new therapeutic strategies.